1987
DOI: 10.1007/bf01885123
|View full text |Cite
|
Sign up to set email alerts
|

Interhepatic duct: A new biliary anomaly

Abstract: True accessory bile ducts occur in only 1% of patients. An accessory bile duct connecting the right and left hepatic ducts at the porta hepatis is described. This anomaly has never been reported previously, and was clinically significant in the presence of partial obstruction of an anomalous right hepatic duct by stones. The embryologic origin of this duct, which we term an "interhepatic duct," is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…No accessory bile ducts were found in the present study, which are described in the literature as having an incidence ranging from 1 to 30% (Benson & Page, 1976;Gibney et al, 1987).…”
Section: Discussionsupporting
confidence: 45%
“…No accessory bile ducts were found in the present study, which are described in the literature as having an incidence ranging from 1 to 30% (Benson & Page, 1976;Gibney et al, 1987).…”
Section: Discussionsupporting
confidence: 45%
“…There is some discrepancy in the reported frequency of this form of anatomical anomaly; some studies quote an incidence of about 1% (Benson and Page, 1976), whereas others claim it to be the commonest type of anomaly of the extrahepatic ducts, occurring in up to 30% of cases (Gibney et al, 1987;Moosman and Coller, 1951). In a detailed autopsy study, Moosman and Coller (1951) found an incidence of 16%, 77% being single and the remaining complex with multiple or branching patterns.…”
Section: Accessory Bile Ductsmentioning
confidence: 82%
“…The following types have been described (Fig. 6): between (1) right hepatic duct and cystic duct (Flint, 1923), (2) right hepatic duct and common hepatic duct, (3) right hepatic duct and neck of the gallbladder (Moosman and Coller, 1951), or (4) the two lobes of the liver (interhepatic duct) (Gibney et al, 1987).…”
Section: Accessory Bile Ductsmentioning
confidence: 99%
“…The common bile duct was absent, and the right hepatic duct emptied directly into the cystic duct. 2 Other cases of communicating extrahepatic biliary ducts have included ducts connecting the right hepatic duct and cystic duct, the right hepatic duct and common hepatic duct, and the right hepatic duct and the neck of the gallbladder. Accessory ducts from the left lobe have been reported that eventually drained into the common hepatic duct.…”
Section: Discussionmentioning
confidence: 99%